2016
DOI: 10.1055/s-0036-1593376
|View full text |Cite
|
Sign up to set email alerts
|

State-of-the-Art Imaging in Pulmonary Embolism: Ventilation/Perfusion Single-Photon Emission Computed Tomography versus Computed Tomography Angiography — Controversies, Results, and Recommendations from a Systematic Review

Abstract: Pulmonary embolism (PE) is a common, ubiquitous, and potentially lethal disease. As symptoms and clinical findings are notoriously nonspecific, diagnostic imaging is essential to avoid undertreatment as well as overtreatment. Controversies remain regarding first-line imaging in suspected PE. The two main contemporary contenders are ventilation/perfusion scintigraphy with single-photon emission computed tomography (V/Q SPECT) with or without additional low-dose CT (SPECT/CT) and CT angiography (CTA). We present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 62 publications
1
11
0
1
Order By: Relevance
“…Similarly, CTA and V/Q scans may have excellent sensitivity and specificity when employed in the proper clinical setting, but CTA may miss peripheral PE and contrast media precludes the use in up to 25% of patients. Whereas the V/Q scan has a high number of inconclusive results if not performed with state-of-the-art SPECT/CT technique, which is not generally abundant [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, CTA and V/Q scans may have excellent sensitivity and specificity when employed in the proper clinical setting, but CTA may miss peripheral PE and contrast media precludes the use in up to 25% of patients. Whereas the V/Q scan has a high number of inconclusive results if not performed with state-of-the-art SPECT/CT technique, which is not generally abundant [8].…”
Section: Discussionmentioning
confidence: 99%
“…¼ of patients and implies considerable radiation exposure, while ventilation/perfusion scintigraphy cannot assess the venous system [8,9].…”
Section: Vte Is a Common Disease With About 1 Million Reported Cases mentioning
confidence: 99%
“…V/Q SPECT is also used as a second line investigation when a CTPA study is non‐diagnostic or has equivocal findings. Recently, a few systematic reviews and meta‐analyses have been published which concluded that V/Q SPECT was superior or equal to CTPA in most clinical settings with better overall diagnostic performance …”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] For young women, pregnant patients, those with impaired renal function and previous contrast reactions, V/Q SPECT is the modality of choice to define or exclude acute pulmonary emboli. [6][7][8] Choosing Wisely clinical decision rules recommend V/Q scans as the first line investigation for acute PE during pregnancy and for women under the age of 55, due to the well documented reduced radiation dose to sensitive breast tissue when compared with CTPA studies. 9,10 V/Q SPECT is also used as a second line investigation when a CTPA study is nondiagnostic or has equivocal findings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation